PENGARUH CURRENT RATIO, NET PROFIT MARGIN DAN EARNING PER SHARE TERHADAP HARGA SAHAM DI BURSA EFEK INDONESIA (Studi Kasus pada Sub Sektor Food and Beverages) - Faleria, Rondonuwu Ester; Lambey, Linda; Walandouw, Stanley Kho (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
With the Indonesia Stock Exchange (IDX), every company's activity in the capital market will make it easier for investors to see the company's financial performance reflecting the financial condition of each reporting company. The capital market becomes an alternative for investors and shareholders to invest funds into companies that are registered on the Indonesia Stock Exchange (IDX). This study aims to examine the influence the variable Current Ratio, Net Profit Margin and Earning Per Share simultaneously and partially to stock prices. The samples in this research are 13 Food and Beverages companies listed in Indonesia Stock Exchange. Results that company financial performance measured by Current Ratio, Net Profit Margin and Earning Per Share do not have significant effect to stock price. t test concluded that the variable of Current Ratio, Net Profit Margin and Earning Per Share do not have significant effect to stock price in manufacturing company of Food and Beverages sub sector. Keywords: Current Ratio, Net Profit Margin, Earning Per Share, Stock Price.